Pembelajaran Terintegrasi “Polos” (Potensi Lokal Sekolah) dalam Peningkatan Minat Belajar IPA Siswa - Nisa, Wilda Muhimmatun (Jurnal Didaktika Pendidikan Dasar, 2022)
Utilizing local potential in learning can make students understand the object of material in daily life, and it's giving a positive impact on higher learning interests. This research aimed to find out students’ interest in learning science after using local potential integrated learning. The subject of the study was a class of students in SMP Negeri 2 Genteng 7th grade, consisting of 32 students. This was Pre Experimental research with One Group Pretest Posttest research design. The sample was chosen by purposive sampling techniques. The instrument used was learning interest questionnaires. The poll was developed by researchers, by showing indicators of learning interest with 23 questions. The data analysis used paired sample t-test and n-gain test. The result shows that the significant value in paired sample t-test is 0.000, lower than 0.05. So, it can be said that local potential integrated learning is significant in increasing students' science learning interests. The average N-gain of student's learning interest increased before and after treatment by 0.60, belonging to moderate criteria.